Determinación de lesiones anatomopatológicas en hígado bovino, faenado en la Empresa Pública Metropolitana de Rastro -Quito - Rodríguez Torres, Paulina de los Ángeles (2015)
This research has a general objective the injury pathological's determination of liver’s cattles and specific objectives: To identify the morphological changes of the organ in some patologies; Set the main macroscopic lesions in the liver. This work was carried out to examined 375 liver's cattle post mortem, and through observation can see if it have any pathology and classify them with types injuries, over a period of 12 days....